latrogenic and Idiopathic Vocal Cord Paralysis: A Real Obligation of Endoscopic Appraisal - A H M Delwar; Nurul Karim Chowdury; Md Shafiqur Rahman; Arif Murshed Khan; ABM Tofazzal Hossain (Global Journals, 2020)
Background: The larynx is an inevitable mouthpiece of the human body which has to execute very associated assignment like protection, respiration, and phonation. To fulfill this mission, the larynx should be accommodated, integrated, and sensible. The vocal cord is the concern of larynx, which served all-purpose. If any occurrence due to iatrogenic, idiopathic, or any other causes shut down the vocal cord mobility, the patient is facing miserable complexity in their life. Methods: It is a cohort retrospective study of 67 cases in the department of otolaryngology and HeadNeck Surgery, Bangladesh, from 01 July 2016 to 31 June 2019.